The efficiency and accuracy of a rapid qualitative tool to ascribe socio-economic status in communities in South Africa – a cross-sectional study. - Nel, Melissa (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.